On the identity of two species of Proctophyllodidae (Acari: Astigmata: Analgoidea) described by Herbert F. Berla in Brazil, with a description of Lamellodectes gen. nov. and a new species - Hernandes, Fabio A. [UNESP] (2014)
Two proctophyllodid species described by Herbert F. Berla were studied, re-described and their generic status was re-eval-uated. A new genus, Lamellodectes gen. nov. (Proctophyllodidae: Pterodectinae), is erected to accommodate Pterodectes ocelatus Berla, 1960 from the White-collared Foliage-gleaner, Anabazenops fuscus (Vieillot) (Furnariidae), and a new species, L. distinctus sp. nov., from the Double-collared seedeater, Sporophila caerulescens (Emberizidae). Proctophyl-lodes minor Berla, 1959a is herein transferred to the genus Platyacarus Kudon, 1982a (Proctophyllodinae) and given a valid name Platyacarus minor (Berla) comb. nov. Updated keys to subfamilies and genera of the family Proctophyllodi-dae are presented. In addition, the known biogeographical distribution for each genus is summarized. Copyright © 2014 Magnolia Press.